2019
DOI: 10.1002/oby.22426
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Metabolic Phenotypes Among Urban Chinese Children: Epidemiology and the Impact of DXA‐Measured Body Composition

Abstract: Objective This study aimed to describe the prevalence rates of abnormal metabolic phenotypes among urban Chinese children and to explore the impact of body composition as measured by dual‐energy x‐ray absorptiometry (DXA) on metabolic disorders. Methods A total of 7,926 children aged 6 to 17 years from seven cities across China were involved. Metabolically unhealthy was defined as having ≥ 2 risk factors (elevated blood pressure, high triglyceride levels, low levels of high‐density lipoprotein cholesterol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
(40 reference statements)
2
19
2
2
Order By: Relevance
“…Secondly, blood pressure was similar in both normal weight children with metabolic abnormalities typical of metabolic syndrome (normal weight metabolically unhealthy [NWMU]) and obese children with metabolic abnormalities (metabolically unhealthy obese [MUHO]), but it was significantly higher than in children with normal body weight who did not suffer from any metabolic abnormalities (normal weight metabolically healthy [NWMH]) and in obese children without metabolic abnormalities (metabolically healthy obese [MHO]). These studies indicate that it is not only adiposity, but disturbed relations between fat mass and lean mass and fat distribution with visceral fatness and metabolic abnormalities that is typical for PH [30,[32][33][34][35]. It also means that even in patients with normal BMI but lower lean mass and relatively greater amount of fat mass with visceral distribution (NWMU), blood pressure was elevated and was accompanied by typical metabolic abnormalities [34].…”
Section: Body Compositionmentioning
confidence: 87%
See 1 more Smart Citation
“…Secondly, blood pressure was similar in both normal weight children with metabolic abnormalities typical of metabolic syndrome (normal weight metabolically unhealthy [NWMU]) and obese children with metabolic abnormalities (metabolically unhealthy obese [MUHO]), but it was significantly higher than in children with normal body weight who did not suffer from any metabolic abnormalities (normal weight metabolically healthy [NWMH]) and in obese children without metabolic abnormalities (metabolically healthy obese [MHO]). These studies indicate that it is not only adiposity, but disturbed relations between fat mass and lean mass and fat distribution with visceral fatness and metabolic abnormalities that is typical for PH [30,[32][33][34][35]. It also means that even in patients with normal BMI but lower lean mass and relatively greater amount of fat mass with visceral distribution (NWMU), blood pressure was elevated and was accompanied by typical metabolic abnormalities [34].…”
Section: Body Compositionmentioning
confidence: 87%
“…Analysis of body composition with the use of dual X-ray densitometry (DXA) showed that the relation between adipose mass and lean body mass is disturbed in hypertensive adolescents [30]. Chen et al, who analyzed body composition in a population sample of Chinese children and adolescents, observed that metabolic abnormalities typical for metabolic syndrome (Table 2) were present in both obese and normal weight children and were associated with VAT rather than BMI [32]. Secondly, blood pressure was similar in both normal weight children with metabolic abnormalities typical of metabolic syndrome (normal weight metabolically unhealthy [NWMU]) and obese children with metabolic abnormalities (metabolically unhealthy obese [MUHO]), but it was significantly higher than in children with normal body weight who did not suffer from any metabolic abnormalities (normal weight metabolically healthy [NWMH]) and in obese children without metabolic abnormalities (metabolically healthy obese [MHO]).…”
Section: Body Compositionmentioning
confidence: 99%
“…The body fat mass of boys increases year by year from the age of 6 to 12, and begins to decrease at the age of 13. However, the increased body fat of girls occurs early in life and is maintained during adolescence, which may be related to the increase of estrogen during puberty [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…За нашими даними, діти з МЗО є достовірно молодшими, ніж з МС, що також підтверджено іншими дослідженнями [31]. Зокрема, китайські дослідники, які обстежили 7926 дітей віком 6-17 років різної тілобудови, показали, що діти з МЗО були молодшими, мали нижчий ІМТ та менші стандартні відхилення ІМТ, менший ОТ [32].…”
Section: вступunclassified
“…Співвідношення ОТС, як маркер ожиріння, був затверджений експертами ВООЗ для дорослих без вікових обмежень і з високою чутливістю у молодих [25]. Ведуться ще дискусії про оцінку цих параметрів у дітей, зокрема більшість досліджень підтримують використання коефіцієнту ОТР менше 0,5 у здорових пропорційних дітей, як і у дорослих [27,40,41], хоча частина дослідників аргументують доцільність використання нижчих значень, задля уникнення хибно-негативних результатів [28,32,39,43]. Чисельними дослідженнями у дітей було протестовано індекс ОТС >0,9 для хлопців шкільного віку, як достовірний критерій ожиріння у дитячому віці [39,43,44] [47,48,49] і були достовірно відмінними між групами обстежених нами пацієнтів.…”
Section: вступunclassified